Cryptosporidium muris in a reticulated giraffe (Giraffa camelopardalis reticulata) - Kodádková, Alena; Kváč, Martin; Ditrich, Oleg; Sak, Bohumil; Xiao, L (The Journal of parasitology, 2010)
Cryptosporidium spp. infection in captive exotic mammals was investigated using staining and molecular biological methods. A total of 323 fecal samples from 100 mammalian species (62 Artiodactyla, 33 Rodentia, 3 Perissodactyla, and 2 Paenungultata) in 4 zoological gardens in the Czech Republic was examined. Only in a reticulated giraffe (Giraffa camelopardalis reticulata) sample was Cryptosporidium sp. infection detected. The partial small subunit rRNA sequence obtained from the isolate was identical to sequences of Cryptosporidium muris in rock hyrax (Procavia capensis) and Bactrian camel (Camelus bactrianus). Neonatal BALB/c mice inoculated with 1 x 10(3) fresh oocysts of the C. muris giraffe isolate did not produce a detectable infection.
Keywords: biotest; Animals; novorozená zvířata; RNA ribozomální; feces; Feces; Prevalence; polymerázová řetězová reakce; Polymerase Chain Reaction; Animals, Newborn; Cryptosporidiosis; Mice; Artiodactyla; Mice, Inbred BALB C; myši; RNA, Ribosomal; prevalence; DNA, Protozoan; Czech Republic; protozoální DNA; myši inbrední BALB C; Biological Assay; Česká republika; zvířata v ZOO; kryptosporidióza; zvířata; Animals, Zoo; Cryptosporidium